2019
DOI: 10.1001/jamacardio.2019.0198
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mortality Data From the Social Security Administration Death Master File for Clinical Research

Abstract: IMPORTANCE Despite its documented undercapture of mortality data, the US Social Security Administration Death Master File (SSDMF) is still often used to provide mortality end points in retrospective clinical studies. Changes in death data reporting to SSDMF in 2011 may have further affected the reliability of mortality end points, with varying consequences over time and by state. OBJECTIVE To evaluate the reliability of mortality rates in the SSDMF in a cohort of patients with atherosclerotic cardiovascular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 15 publications
1
34
0
Order By: Relevance
“…Other limitations include the possibility of underestimating mortality in our population as the use of the Social Security Death Index may underestimate overall mortality . In addition, Hispanics returning to their birth countries prior to their death would not be reflected in the National Death Index leading to a possible underestimation of mortality in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Other limitations include the possibility of underestimating mortality in our population as the use of the Social Security Death Index may underestimate overall mortality . In addition, Hispanics returning to their birth countries prior to their death would not be reflected in the National Death Index leading to a possible underestimation of mortality in this group.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that the SSA Death Master File may underestimate actual mortality rates. 35 We attempted to address this by supplementing SSA data with EHR death information; however, some misclassification may still exist.…”
Section: Discussionmentioning
confidence: 99%
“…With the institution of the 2011 Social Security Administration's (SSA) ruling that it could not release state owned data to the Social Security Death Masterfile (SSDMF), 3 4 changes in the completeness of the SSDMF, and a resulting great reduction in the number of deaths included in the releasable file, 5 6 the need for understanding the validity of linkages with other major sources of death data used for research has increased. Our work helps address uncertainty about linkages with these death databases and thus strengthens clinical and health policy decisions arising from their usage.…”
Section: Background and Significancementioning
confidence: 99%